Peningkatan Pengetahuan Melalui Pelatihan Pertolongan Pertama pada Cedera di Sekolah dengan Metode Peer Teaching - Oktavianisya, Nelyta; Aliftitah, Sugesti (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2023)
Injuries due to accidents in the school environment are very common and varied, such as slips that cause lacerations or bruises, dislocations to fractures (fractures), food poisoning, choking on food, fainting and others. First aid in an accident is an effort to help and temporarily treat accident victims before getting more complete help from a doctor or paramedic. The aim of this study was to determine the effect of first aid training on injuries in schools with the Peer Teaching method on the level of knowledge. The research design is a pre-experimental, one group pre-post test design. The sample in this study was 52 respondents with the sampling technique used was the simple random sampling technique. The independent variable is first aid training for injuries at school using the Peer Teaching method and the dependent variable is the level of knowledge. The instrument to measure knowledge level using Questionnaire. The data was analyzed using the Paired Samples T test. The results showed that the average level of knowledge after exercise was increased by 9.33. The results of the pretest-posttest data analysis of the level of knowledge using the Paired Samples T Test obtained the ρValue = 0.001 with α = 0.05. Because ρValue <α, there is an effect of first aid training on injuries at school on increasing knowledge with the peer method. By conducting training on students, it is hoped that students will be more confident and motivated to help injuries at school.